Temporal Control of Axonal Transport: The Extreme Case of Organismal Ageing - Mattedi, Francesca; Vagnoni, Alessio (Frontiers in Cellular Neuroscience, 2019)
A fundamental question in cell biology is how cellular components are delivered to their destination with spatial and temporal precision within the crowded cytoplasmic environment. The long processes of neurons represent a significant spatial challenge and make these cells particularly dependent on mechanisms for long-range cytoskeletal transport of proteins, RNA and organelles. Although many studies have substantiated a role for defective transport of axonal cargoes in the pathogenesis of neurodevelopmental and neurodegenerative diseases, remarkably little is known about how transport is regulated throughout ageing. The scale of the challenge posed by ageing is considerable because, in this case, the temporal regulation of transport is ultimately dictated by the length of organismal lifespan, which can extend to days, years or decades. Recent methodological advances to study live axonal transport during ageing in situ have provided new tools to scratch beneath the surface of this complex problem and revealed that age-dependent decline in the transport of mitochondria is a common feature across different neuronal populations of several model organisms. In certain instances, the molecular pathways that affect transport in ageing animals have begun to emerge. However, the functional implications of these observations are still not fully understood. Whether transport decline is a significant determinant of neuronal ageing or a mere consequence of decreased cellular fitness remains an open question. In this review, we discuss the latest developments in axonal trafficking in the ageing nervous system, along with the early studies that inaugurated this new area of research. We explore the possibility that the interplay between mitochondrial function and motility represents a crucial driver of ageing in neurons and put forward the hypothesis that declining axonal transport may be legitimately considered a hallmark of neuronal ageing.